2015
DOI: 10.1208/s12249-015-0293-1
|View full text |Cite
|
Sign up to set email alerts
|

Size Control in the Nanoprecipitation Process of Stable Iodine (127I) Using Microchannel Reactor—Optimization by Artificial Neural Networks

Abstract: Abstract. In this study, nanosuspension of stable iodine ( 127 I) was prepared by nanoprecipitation process in microfluidic devices. Then, size of particles was optimized using artificial neural networks (ANNs) modeling. The size of prepared particles was evaluated by dynamic light scattering. The response surfaces obtained from ANNs model illustrated the determining effect of input variables (solvent and antisolvent flow rate, surfactant concentration, and solvent temperature) on the output variable (nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…To date, some foreign scholars have used neural networks to optimise the reaction performance of microreactors. For example, Aghajani used an artificial neural network to research the size of synthesised nano-iodine in microreactors; it was found that the relationships between flow rate of solvent, flow rate of antisolvent, and size of the synthesised nano-iodine are in inverse relation [21]. Na researched the optimisation of catalyst loading in Fischer-Tropsch microchannel reactors, using the distribution of catalyst loading in microchannel reactors as a variable and considering C5+ productivity and temperature rise in microchannels as optimisation objects by using computational fluid dynamics, it was found that C5+ productivity was increased to 22% and ΔTmax was decreased to 63.2% by using a genetic algorithm (GA) [22].…”
Section: Nomenclaturementioning
confidence: 99%
“…To date, some foreign scholars have used neural networks to optimise the reaction performance of microreactors. For example, Aghajani used an artificial neural network to research the size of synthesised nano-iodine in microreactors; it was found that the relationships between flow rate of solvent, flow rate of antisolvent, and size of the synthesised nano-iodine are in inverse relation [21]. Na researched the optimisation of catalyst loading in Fischer-Tropsch microchannel reactors, using the distribution of catalyst loading in microchannel reactors as a variable and considering C5+ productivity and temperature rise in microchannels as optimisation objects by using computational fluid dynamics, it was found that C5+ productivity was increased to 22% and ΔTmax was decreased to 63.2% by using a genetic algorithm (GA) [22].…”
Section: Nomenclaturementioning
confidence: 99%
“…Since nanosuspension of stable-iodine ( 127 I) is a deflocculated nanosuspension [7], sedimentation time of formulation can be easily determined by visual observation of a densely packed sediment during a certain period of time as the sedimentation time. In other words, sedimentation time of samples was considered as phase separation time of nanoparticles in nanosuspension, representing an indicator of physical stability [10].…”
Section: Evaluation Of Sedimentation Timementioning
confidence: 99%
“…Since nanosuspension of stable-iodine ( 127 I) is a deflocculated suspension, we used visual observation of sediment to evaluate stability of samples obtained, as mentioned in previous studies [7,10,14]. In a deflocculated suspension, a densely packed sediment with a slow sedimentation rate has a hard structure and cannot be re-dispersed after shaking.…”
Section: Evaluating the Effect Of Input Variables On Sedimentation Timentioning
confidence: 99%
See 2 more Smart Citations